Manajemen Pendidikan Musik: Pengalaman dan Persepsi Guru Musik SMA di Kota Palangka Raya - Ratih Sulistyowati (Musikolastika: Jurnal Pertunjukan dan Pendidikan Musik, 2024)
Purpose: This study aims to provide an overview of music teachers' experiences and perceptions of music education management in the schools where they teach in Palangka Raya City. Methods: This article uses a descriptive qualitative approach and involves music teachers from five high schools in Palangka Raya City as participants. Data were collected through interviews and observations, then analyzed through the stages of data reduction, data presentation, conclusion drawing, and data verification. Results and Discussion: The results showed that music teachers faced various challenges in carrying out their duties, especially limited resources. However, the music teachers also achieved successes in carrying out their duties, such as increasing students' interest in music, creating a creative learning environment, and improving students' ability to understand music. This study also shows that music teachers have hopes and needs for future music education management, such as increased resources and improved curriculum quality. Conclusion: The results of this study can provide insights for teachers in developing better music education management approaches, help school principals in providing the necessary resources and support to improve music education management, and can provide insights for other music education researchers and practitioners on important issues in music education management at the high school level, especially in Palangka Raya City.